(untitled) (Global Journal of Science Frontier Research, 2024)
This paper is concerned with frontiers as spaces of disputed ceded suspended or imposed forms of rule that challenge the integrity of bounded territorial polities and their jigsaw puzzle-limits In recent decades frontiers have received increased attention perhaps due to the growing importance marginal and ungoverned spaces have acquired within the global economy In spite of their enormous diversity of climates landscapes and societies frontiers in Latin America have historically been described and intervened in surprisingly similar ways The idea of the frontier is here so intertwined with the reality of these places that they have become indistinguishable This article explores the production of frontiers more than as a type of space as an object of common sense and intervention From an ontological point of view its aim is to problematize the way frontiers are produced and enacted as an object constituted and enacted in practice by dissecting its constitutive practices what is categorized as a frontier how is it categorized and its constitutive relations the conditions and possibilities created by the frontier that empower certain groups and create new systems of access and control of land and resources